2018
DOI: 10.1101/323428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prefrontal co-expression of schizophrenia risk genes is associated with treatment response in patients

Abstract: Gene co-expression networks are relevant to functional and clinical translation of schizophrenia (SCZ) risk genes. We hypothesized that SCZ risk genes may converge into coexpression pathways which may be associated with gene regulation mechanisms and with response to treatment in patients with SCZ. We identified gene co-expression networks in two prefrontal cortex post-mortem RNA sequencing datasets (total N=688) and replicated them in four more datasets (total N=227). We identified and replicated (all p-value… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…Polygenic co-expression index calculation. Recent publications have shown that gene sets defined using co-expression networks and selected for their association with the genes DRD1 and DRD2 provided replicable predictions of n-back-related brain activity and behavioral indices in line with the role of prefrontal dopamine in working memory 27,[88][89][90] . The gene sets have been previously identified using weighted Gene Co-expression Network Analysis [WGCNA 28 ] applied on the Braincloud dataset (N = 199) of post-mortem DLPFC gene expression 29 resulting in 67 non-overlapping sets of genes based on their expression pattern.…”
Section: Gene-based Pcismentioning
confidence: 97%
“…Polygenic co-expression index calculation. Recent publications have shown that gene sets defined using co-expression networks and selected for their association with the genes DRD1 and DRD2 provided replicable predictions of n-back-related brain activity and behavioral indices in line with the role of prefrontal dopamine in working memory 27,[88][89][90] . The gene sets have been previously identified using weighted Gene Co-expression Network Analysis [WGCNA 28 ] applied on the Braincloud dataset (N = 199) of post-mortem DLPFC gene expression 29 resulting in 67 non-overlapping sets of genes based on their expression pattern.…”
Section: Gene-based Pcismentioning
confidence: 97%
“…Previous publications have shown that gene sets defined using co-expression networks and selected for their association with the genes DRD1 and DRD2 provided replicable predictions of n-back-related brain activity and behavioral indices (23,(25)(26)(27). Weighted Gene Co-expression Network Analysis [WGCNA (28)] applied on the Braincloud dataset (N=199) of post-mortem DLPFC gene expression ( 29) identified 67 nonoverlapping sets of genes based on their expression pattern.…”
Section: Polygenic Co-expression Index Calculationmentioning
confidence: 99%